HUBUNGAN ANTARA NYERI REUMATOID ARTRITIS DENGAN KEMANDIRIAN ADL PADA LANSIA - Kartini Kartini; Elisabeth Samaran; A Marcus (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2018)
Arthritis or commonly called rheumatism is a disease that attacks the joints and surrounding structures. Rheumatic disease in the community is often considered a trivial disease because it does not cause death, but if not treated quickly rheumatism can make limbs function abnormally, starting from bumps, stiff joints, difficulty walking, even lifelong disability. Objective: to find out there is a relationship between rheumatoid arthritis pain and independence of Activity daily living (ADL) in the elderly. Research Methods: This study used a quantitative research design with a cross sectional approach to reveal the relationship between independent variables (Rheumatoid Arthritis pain) and the dependent variable of Independent Activity daily living (ADL) at the same time and once a measurement. Statistical tests using chi-square consisted of 33 respondents. Results: From the results of the chi-square statistical test obtained p value = 0.047 (p <0.05) there was a relationship between rheumatoid arthritis pain and the independence of the elderly in the puskesmas classaman city of Sorong. Conclusion: There is a relationship between Rheumatoid Arthritis pain and the degree of independence in carrying out daily life activities in the elderly in the working area of ​​the Sorong City Community Health Center (p value = =, 047) Keywords: Rheumatoid Pain Arthritis; Elderly ADL Bibliography: 2002 – 2017